URGENSI INTEGRASI ANTARA MEDIASI DAN HAKAM DALAM PENYELESAIAN PERKARA PERCERAIAN DENGAN ALASAN SYIQAQ DI PENGADILAN AGAMA - Huzaimah, Arne (Universitas Islam Negeri Raden Fatah Palembang, 2016)
Settlement of disputes divorce on the grounds “syiqaq” have two mechanisms for peace, which is mediating in the initial examination of the case and making the appointments “hakam” were carried out after the process of verification. Mediator and “hakam” same function, namely as a neutral party to reconcile the two sides of a dispute. This of course raises another problem where the dualism of law and overlapping carried out by two different agencies in one point. When taken in conjunction with the principle of justice that is simple, fast and inexpensive, of course, can lead to the length and complexity of the dispute resolution process for divorce on the grounds “syiqaq” between mediation and “hakam” have mechanisms respectively. Although on the other hand, the institution of mediation and “hakam” was to embody the principle of compulsory reconciling the parties in the process of judicial civil procedure law agama. In addition, in spite of the mediation and the appointment of “hakam” in the dispute resolution process of divorce on the grounds “syiqaq” as an attempt to reconcile the two parties dispute, but peace efforts have not achieved the expected results, the divorce rate remains high and even increasing every year. Therefore, there should be integration between mediation and “hakam” as a single entity in the settlement process of a divorce on the grounds “syiqaq”. Urgency integration between mediation and “hakam” in the completion of a divorce case on the grounds “syiqaq” are to: simplifies the process of settlement of a divorce case on the grounds “syiqaq”; Religious Court of Justice to embody the principle is simple, quick and inexpensive; re-establish the Islamic shariah on the mechanism for settling disputes “syiqaq” in the religious and synergize with positive law in Indonesia; and the last to discuss for alternatives in addressing divorce rate in Indonesia.